Subsurface Marine Heatwaves of South Java Sea: Trend, Frequency, Duration, and Cumulative Intensity Based on Assimilation Model (1993-2019) - Azuga, Nabila Afifah; Radjawane, Ivonne M. (Faculty of Fisheries and Marine, Universitas Riau, 2022)
Marine heatwaves (MHWs) are extreme warming events in the ocean when the temperature detected is above the 90th percentile of climatological temperature for at least five consecutive days. MHWs events can extend up to thousand kilometers and have been detected in the subsurface layer. MHWs are described by metrics (frequency, duration, and cumulative intensity). The purpose of this study was to determine the characteristics of MHWs in the subsurface layer for 27 years (1993-2019). The data used in this study is the sea water temperature data of the depth 0,4m-763m from Marine Copernicus Global Ocean Physics and Niño 3.4 indices. The method used in this study is a statistical method to calculate the average and trend of the MHWs metric. The results of this study denotes that the occurrence of MHWs at a depth of 0.4m-92m is caused by ENSO (El Niño Southern Oscillation) positive phase (El Niño) with a delay of 7-8 months and at a depth of 109m-763m caused by negative phase ENSO (La Niña) with a delay of 1-3 months. It was also found that the frequency of MHWs was higher at a depth of 418m-763m with a maximum value is 2,6 events/year, the duration of MHWs was greater at a depth of 0,4m-77 m, with a maximum value of duration is 30-32 days/year, and the maximum cumulative intensity of MHWs events for 27 years is 90˚C. During the 1993-2019, the trend of frequency, duration, and cumulative intensity of MHWs in the subsurface layer of south Java Sea has significantly increased.